PENGEMBANGAN MEDIA PEMBELAJARAN “PECI” (PEMIMPIN CILIK BERAKSI) APLIKASI BERBASIS WEB UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI PERJUANGAN DAKWAH RASULULLAH DI MEKKAH - Dila Sekar Dahlia; Alista Dwiyanti; Abdul Rozak; Muhammad Fadhli Sayyid Abdillah; Ani Nur Aeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the need for learning that aligns with the characteristics of Generation Alpha at the elementary school level, who prefer visual, interactive, and technology-based learning. In practice, Islamic Religious Education, especially the Prophet Muhammad's Da'wah Struggle in Mecca, is still dominated by lecture methods and textbooks, resulting in relatively low student interest and understanding. This study aims to develop an Android-based digital learning media called “PECI” (Pemimpin Cilik Beraksi) to improve student engagement and comprehension. The method used is Research and Development (R&D) with the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The trial subjects consisted of 11 third-grade students of SDN Tanjungmekar. Research instruments included material and media expert validation sheets, as well as pretest and posttest questions. The validation results indicated that the media was categorized as highly feasible with an average score of 91.25% from material experts and 93.75% from media experts. The implementation of the media through interactive learning videos and quizzes showed increased student activity and enthusiasm during the learning process. Statistical analysis using paired sample t-test showed a significant difference between pretest and posttest scores (p < 0.05). In addition, the average N-gain score of 0.530 was categorized as moderate, indicating an improvement in students’ understanding. Thus, the Android-based PECI media is considered effective and feasible as an innovative Islamic Religious Education learning tool to improve understanding and character development of elementary school students.